A robust control scheme to enhance the stability of a grid-connected large scale photovoltaic system - Islam, G.; Al-Durra, A.; Muyeen, S.M.; Tamura, J. (2012)
This paper presents a new robust control strategy to improve the steady-state and transient stabilities of a grid connected large scale photovoltaic (PV) system. The grid codes for PV system to provide dynamic grid support are getting stricter due to the substantial increase in the power generation from grid connected PV systems, in recent years. The proposed control scheme helps quick voltage recovery against different types of symmetrical and unsymmetrical faults and ensures a good DC link overvoltage protection. Detailed modeling for individual components of a grid connected large scale PV system are carried out using PSCAD/EMTDC to analyze the performance of the proposed strategy.